THE EFFECT OF WHITE DRAGON FRUIT (HYLOCEREUS UNDATUS) SIMPLICIA AS A CARDIOPROTECTIVE AGENT IN WHITE RATS (RATTUS NORVEGICUS) ADMINISTERED DEXAMETHASONE - Syakira, Aprilia Anggun; Samsuri,; Damriyasa, I Made; Raharjo, Yudha Yaksa Crada Yoga Arum; Unique, I Gusti Ayu Nadia Prasta (Buletin Veteriner Udayana, 2026)
Long-term dexamethasone use may induce cardiovascular side effects, such as oxidative stress and myocardial damage, which manifest as degeneration, necrosis, and inflammation. White dragon fruit (Hylocereus undatus) contains polyphenols, flavonoids, betalains, and vitamin C, which possess strong antioxidant properties and may have cardioprotective effects. This study aimed to evaluate the effects of white dragon fruit simplicia on cardiac histopathology in dexamethasone-treated rats (Rattus norvegicus). Twenty-five Wistar rats were divided into four groups: P0 (negative control), P1 (positive control – dexamethasone 0.13 mg/kg), P2 (dexamethasone + 50% simplicia), and P3 (dexamethasone + 100% simplicia). The treatments were administered orally for 21 days. Cardiac tissue was processed using hematoxylin and eosin staining to assess degenerative, necrotic, and inflammatory changes. Statistical analysis was performed using the Kruskal-Wallis and Mann–Whitney tests. The results of the Mann–Whitney test on the degeneration parameters showed a significant difference between the negative control group (P0) and groups P1, P2, and P3. In the necrosis parameter, the Mann–Whitney test results showed a significant difference between P0 and P1, but no significant difference between P2 and P3. None of the treatment groups showed significant differences in the inflammation parameters (p > 0.05). It can be concluded that the administration of white dragon fruit (Hylocereus undatus) simplicia was able to significantly reduce the severity of necrotic lesions, as well as reduce the degree of degeneration, especially at a dose of 100%, but did not have a significant effect on inflammatory lesions in the hearts of white rats (Rattus norvegicus) treated with dexamethasone.